Utilization of sawdust on the compressive strength of concrete with variations of cement - Zulmahdi Darwis; Hendrian Budi Bagus Kuncoro; Axel Xavier Delpiero (Faculty of Engineering, Universitas Sultan Ageng Tirtayasa, 2022)
The construction process requires building materials so that the buildings made can last a long time and cannot be planned. Concrete is the most widely used material in the manufacture of buildings; therefore, a strong and quality concrete material can produce strong concrete according to the plan. As a replacement for each kind of cement, this research aimed to see how bayur sawdust affected concrete strength and find out which amount of sawdust, ranging from 0% to 2.0% of the cement weight, had the maximum compressive strength. The test object is a cylinder with a diameter of 15 cm and a height of 30 cm with 54 specimens. The cement used in this research is 2 (two) Indonesian Cement Manufacturers and 1 (one) Chinese Cement Manufacturer. The results of research conducted from the use of sawdust fibre concrete as much as 0%, 1.0%, and 2.0% of the weight of each (brand) cement, namely the average compressive strength value of Cement Manufacturing Indonesia 1, which is 21.14 MPa, 17.90 MPa, and 22.40 MPa. The average compressive strength of Cement Manufacturer Indonesia 2 is 20.63 MPa, 17.53 MPa, and 21.36 MPa. The average compressive strength of Cement Manufacturers in China is 21.72 MPa, 19.50 MPa, and 23.01 MPa. This study's compressive strength test data showed that the composition between China Factory Cement and 2% sawdust had the most optimal value because it produced the largest compressed concrete, which was 23.01 MPa. Proses konstruksi bangunan memerlukan bahan bangunan yang kokoh agar bangunan yang dibuat dapat bertahan lama dan dapat memikul beban yang telah direncanakan. Beton merupakan bahan yang paling banyak dipakai dalam pembuatan bangunan, oleh sebab itu material penyusun beton yang kuat dan berkualitas dapat menghasilkan kuat tekan beton yang sesuai dengan rencana. Tujuan penelitian ini adalah untuk mengetahui pengaruh serbuk kayu bayur sebagai bahan pengganti sebagian dari variasi setiap semen terhadap kuat tekan beton dan mengetahui nilai kuat tekan beton terbesar dari variasi serbuk kayu sebesar 0%, 1.0%, dan 2.0% terhadap berat setiap variasi semen yang digunakan. Benda uji berbentuk silinder berdiameter 15 cm dan tinggi 30 cm dengan benda uji sebanyak 54 buah. Semen yang digunakan dalam penelitian ini yaitu 2 (dua) Semen Pabrikan Indonesia dan 1 (satu) Semen Pabrikan China. Hasil penelitian yang dilakukan dari penggunaan beton serat serbuk kayu sebanyak 0%, 1.0%, dan 2.0% dari berat setiap (merk) semen yaitu didapat nilai kuat tekan rata-rata dari Semen Pabrikan Indonesia 1 yaitu 21.14 MPa, 17.90 MPa, dan 22.40 MPa. Hasil rata-rata kuat tekan dari Semen Pabrikan Indonesia 2 yaitu 20.63 MPa, 17.53 MPa, dan 21.36 MPa. Hasil rata-rata kuat tekan dari Semen Pabrikan China yaitu 21.72 MPa, 19.50 MPa, dan 23.01 MPa. Data pengujian kuat tekan beton pada penelitian ini menunjukkan komposisi antara Semen Pabrikan China dengan serbuk kayu 2% memiliki nilai yang paling optimal karena menghasilkan kuat tekan beton terbesar yakni 23.01 MPa.